Light-powered micromotor: synthesis, motion behaviour and applications / Ts. Mohamed Syazwan Osman and Muhammad Ismail - Osman, Mohamed Syazwan; Ismail, Muhammad (2020)
Photocatalytic micromotors or light powered micromotors have been studied intensively for the past few years for several applications such as environmental remediation, biomedicine and micropumps. In water remediation, conventional wastewater treatment has been known for its economically infeasible. Therefore, a different approach by using micromotor as the possible substitute for water remediation has been focused on. Throughout the years, a substantial number of researches has been done in the synthesis of these light-powered micromotors which revolves around its materials used, motion behavior and its applications. Hence, this paper focus on the progress of light-powered micromotors which will focus on the synthesis method, motion behavior and its applications.